WOMEN, ART & POLITICS IN PAKISTAN: RETHINKING FEMINISM THROUGH FEMINIST ART - Kamran, Sadia Pasha (PEOPLE: International Journal of Social Sciences, 2019)
This paper looks into the contemporary art practice in Pakistan and tries to cognize feminist art and feminist aesthetics in local context with a belief that feminist aesthetics ultimately answers the issues of feminism itself. In its broader scope the study looks at the works of selected women artists, most of them actively involved with the Women Action Forum (WAF), in order to theorize feminist aesthetics which must re-define feminism and feminist’s concerns in the present day Pakistan where like elsewhere women affairs have become a pertinent issue. The paper negates the popular notion that feminist art must address the controversial issues of ‘social morality’ and/or it is all about agendas of the leftists against any established cultural norms. Feminist art in Pakistan exhibits a flavor of its own which is somewhat different than the Western notions.